Looking at Arctic tourism through the lens of cultural sensitivity : ARCTISEN – a transnational baseline report - Olsen, Kjell O.; Avildgaard, Mette S.; Brattland, Camilla; Chimirri, Daniela; De Bernardi, Cecilia; Edmonds, Johnny; Grimwood, Bryan S. R.; Hurst, Chris E.; Höckert, Emily; Jæger, Kari; Kugapi, Outi; Lemelin, R. Harvey; et al. (fi=Lapin yliopisto|en=University of Lapland|, 2019)
publishedVersion